Prognostic Value of KRAS Mutation Status in Libyan Patients with Colorectal Cancer (مجلة الرازي الطبية, 2026)
Colorectal cancer (CRC) remains a major public health issue. The identification of markers that affect CRC prognosis is of great importance. KRAS mutations play a crucial role in carcinogenesis with a powerful predictive value. The present study investigated the associations of KRAS mutation status with clinicopathological variables and survival outcomes in Libyan patients with CRC. The clinicopathological variables of 168 patients with CRC diagnosed at the National Cancer Institute in Misurata, Libya, between 2010 and 2018 were retrospectively investigated. Tumour tissue samples were analyzed at Biomnis, Lyon, France (LCD-Array kit). The results were categorized into two groups: KRAS wild-type (KRAS WT) and KRAS mutant-type (KRAS MT). The relationships between KRAS mutation status and clinicopathologic variables and survival outcomes were analyzed using the Kaplan-Meier method, log-rank test, and Cox regression test.  KRAS wild-type (WT) was detected in 52.4% of patients, while KRAS mutant-type (MT) was found in 47.6. KRAS MT was significantly associated with more indicators of a malignant phenotype, including a high-grade tumour, large tumour size, positive lymph nodes, advanced stage, distant metastasis, surgically unresectable tumour, and high expression of carcinoembryonic antigen (CEA). Regarding survival, patients with KRAS MT had shorter overall survival rates (P < 0.0001, log-rank) and lower disease‑free survival rates (p=0.001, log‑rank). Multivariate analysis showed that KRAS MT (P